Distributed Signal Processing Techniques for Wireless Sensor Networks. (11th February 2008) - Serpedin Serpedin, Erchin Erchin; Li Li, Hongbin Hongbin; Dogandžić Dogandžić, Aleksandar Aleksandar; Dai Dai, Huaiyu Huaiyu; Cotae Cotae, Paul Paul
Abstract :